Ethics: The Elixir of Publications - Manphool Singhal; Suprit Basu; Arun Sharma; Paramjeet Singh (Indian Journal of Radiology and Imaging)
Scientific papers are the driving force for research, information dissemination, and policymaking that directly impacts society. Thus, ethical practices are the elixir of publications. Adherence to ethical practices promotes integrity in research and publication. Transgression of ethics is thus considered a poison to science. Although there is no definition of ethics, it includes a systematic approach that not only recommends but also defends and protects concepts of the conduct of right and wrong. Therefore, ethical principles should be strictly adhered to and upheld at any cost for the progression of science. This article addresses various actions that are considered ethical misconduct and guidelines to fix them. Recommendations of various organizations related to the ethics in publications are also discussed.